Pengendalian Pencemaran Udara - Ristia, Yutami (Jurnal El-Thawalib, 2022)
This research is motivated by the rubber management process carried out by PT.Virco, air and water pollution problems arise which result in complaints from Aek Tampang residents, causing implementation that is not in accordance with existing regulations.The formulation of the problem in this study is how to implement Regional Regulation Number 02 of 2011 Article 12 Paragraph (1) concerning Air Pollution Control in Rubber Waste Management by the Padangsidimpuan City Environmental Service. This study aims to determine the implementation of Regional Regulation Number 02 of 2011 Article 12 Paragraph (1) concerning Control of Air Pollution in Rubber Waste Management by the Regional Environmental Service of Padangsidimpuan City.This type of research is field research, which describes and describes the situation and phenomena more clearly regarding the situation that occurs, then the type of research used is a qualitative research type. Meanwhile, the approach used in this research is qualitative and descriptive. The results of the study stated that the implementation of Regional Regulation Number 02 of 2011 Article 12 Paragraph (1) concerning Control of Air Pollution in Rubber Waste Management by the Regional Environmental Service of Padangsidimpuan City has not been implemented, this can be seen from the form of implementation that has not been implemented by the Regional Environmental Service. The city of Padangsidimpuan.